Dynamics of Political Communication between Megawati and Puan Maharani in the Leadership of the Partai Demokrasi Indonesia Perjuangan - Hasan, Fahmi; A'rifa'i, Hariz; Kartika, Tina; Trenggono, Nanang (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study analyzes the dynamics of political communication between Megawati Soekarnoputri and Puan Maharani in the leadership of the Indonesian Democratic Party of Struggle (PDIP). Using a descriptive-analytical approach and Symbolic Interactionism theory, this research highlights the importance of symbols in shaping public perception of both leaders. The results of the analysis indicate that their political interactions influence the party's image, especially in the context of specific political events such as elections and policy controversies. The interpretation of political communication symbols also reveals the complexity of public perception towards the PDIP and its leaders. The implications for the PDIP leadership in facing political challenges, including coalition formation, underscore the importance of responsive and effective communication strategies. This study provides valuable insights into the dynamics of Indonesian politics and makes a significant contribution to understanding political communication and party dynamics in the country.